The Standard Data and their Limitations - Deschênes, Jean-Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1957)
SummaryIn this article, the author considers the possibility of using standard data in setting standard times to perform a specific job. Where and when can those data be used? Before answering these questions, he describes the procedure to be followed in applying this method and insists on the limitations of its application, taking into account the data themselves, the operator and the study man.